2020
DOI: 10.1186/s12871-020-01154-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk of postoperative nausea and vomiting in hip and knee arthroplasty: a prospective cohort study after spinal anaesthesia including intrathecal morphine

Abstract: Background The overall risk of postoperative nausea and vomiting after general anaesthesia is approximately 30% even with prophylactic medications. Studies exploring the risk after regional anaesthesia including intrathecal morphine are limited but indicate that intrathecal morphine is highly emetogenic and is additive to the PONV risk associated with other forms of anaesthesia. The aim of this observational study was to investigate the risk of PONV after spinal blockade combined with intrathecal morphine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
1
4
3
Order By: Relevance
“…The recent prospective observational study reported female sex and a history of PONV as signi cant risk factors for PONV after spinal anesthesia [12]. Although this study did not show a signi cant association between smoking and PONV incidence due to a lack of smokers [12], our study also showed a signi cant association between them. The effect of postoperative opioid on PONV after spinal anesthesia could be estimated from previous studies regarding opioidsparing analgesia in spinal anesthesia [13], and postoperative opioid also showed a signi cant association with PONV incidence after spinal anesthesia in our study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The recent prospective observational study reported female sex and a history of PONV as signi cant risk factors for PONV after spinal anesthesia [12]. Although this study did not show a signi cant association between smoking and PONV incidence due to a lack of smokers [12], our study also showed a signi cant association between them. The effect of postoperative opioid on PONV after spinal anesthesia could be estimated from previous studies regarding opioidsparing analgesia in spinal anesthesia [13], and postoperative opioid also showed a signi cant association with PONV incidence after spinal anesthesia in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…Our result suggested that four risk factors for PONV included in the Apfel score could be still valid for predicting PONV after spinal anesthesia [7]. The recent prospective observational study reported female sex and a history of PONV as signi cant risk factors for PONV after spinal anesthesia [12]. Although this study did not show a signi cant association between smoking and PONV incidence due to a lack of smokers [12], our study also showed a signi cant association between them.…”
Section: Discussioncontrasting
confidence: 53%
“…This is perhaps due to chewing gum having no supplementary anti-emetic effect or perhaps neuraxial anaesthesia with spinal morphine playing a significant role in the incidence of PONV compared to general anaesthetic. Patients undergoing lower limb surgery under spinal anaesthesia combined with intrathecal Morphine had a similar incidence of PONV to that in our study [17]. Trials assessing the non-inferiority of chewing gum compared to Ondansetron in treatment of PONV after LSCS may shed more light on this subject.…”
Section: Discussionsupporting
confidence: 67%
“…Our result suggests that four risk factors for PONV included in the Apfel score could be still valid for predicting PONV after spinal anesthesia [ 7 ]. The recent prospective observational study reported female sex and a history of PONV as significant risk factors for PONV after spinal anesthesia [ 12 ]. This previous study did not show a significant association between smoking and PONV incidence due to a lack of smokers [ 12 ]; however, our study revealed a significant association between them.…”
Section: Discussionmentioning
confidence: 99%